(untitled) (FULafia Journal of Science and Technology, 2018)
The influences of microwave heating (Microwave oven Electrolux, model EMM2005, 2450 MHz, 400 W) and thermal heating (Hot plate Thermostat, Temperature range: 25 to 125oC) for 30 min on the oxidation of groundnut oil (Arachis hypogaea) and palm oil (Elias guineensis) were studied. The heating treatments increased dry matter and oils contents at given conditions and therefore, with reduced moisture content. Analyses of the two oils determined were the acid values, peroxide values, saponification and iodine values using the method of analysis of Association of Official Analytical Chemists (AOAC). Except saponification values, all the chemical properties of the two oils from different heating treatments showed no significant (p<0.5) variations over the temperature ranges